Предмет: Алгебра,
автор: slavkopon123
9(3(х+1)-2х)=7(х+1) решить уравнение
slavkopon123:
сроочно
Ответы
Автор ответа:
1
Ниже основное решение. Ответ -10
Приложения:
Автор ответа:
1
Ответ:
9(3(x+1)-2x)=7(x+1)
9(3x+3-2x)=7x+7
27x+27-18x=7x+7
9x+27=7x+7
9x-7x=7-27
2x=-20
X=-20/2
X=-10
Объяснение:
Похожие вопросы
Предмет: Другие предметы,
автор: Вишня25
Предмет: Українська література,
автор: mk050881pkm
Предмет: Русский язык,
автор: Анюта2001
Предмет: Алгебра,
автор: lina395
Предмет: Математика,
автор: sandarapavlova